L’impact Des Systèmes D’information Sur La Performance Des Chaines Logistiques: Une Revue De Littérature - Ouariti, Ouafae Zerouali; Zeroual, Laila (European Scientific Journal, ESJ, 2017)
In the context of global competition which is characterized by a variety of products, short life cycles, and a competitive pressure between the supply chains, the cooperation and collaboration between companies has become very crucial. These collaborative relations improve the coordination of activities within the supply chains and have resulted to a higher performance through the use of information systems. These information systems have enabled it to face the rise in the complexity of the logistics sector which was born out of the information. To better position our contribution, we made a review of the literature and defined the variables and the hypotheses of this research work.